A review on computer vision based defect detection and condition assessment of concrete and asphalt civil infrastructure. Issue 2 (April 2015) - Koch, Christian; Georgieva, Kristina; Kasireddy, Varun; Akinci, Burcu; Fieguth, Paul
Highlights Visual inspection of civil infrastructure is essential for condition assessment. We focus on concrete bridges, tunnels, underground pipes, and asphalt pavements. Accordingly, we review the latest computer vision based defect detection methods. Using computer vision most relevant types of defects can be automatically detected. Automatic defect properties retrieval and assessment has not been achieved yet.